Guitar in São Paulo: information on the instrument in the imperial period (Orfeu, 2023)
The present article brings notes on the guitar in São Paulo in Imperial Brazil (1822-1889). Due to the lack of information and bibliography about the subject, primary sources were used (newspapers, magazines), fiction and history books, memoirs and biographies as also. The information collected points to a movement around the guitar that can be associated to the activities of the law course established in the city (1828). The diffusion of methods, sale of instruments, performances and composers were detected. The information allows the identification of a social network linked to the instrument, and it was possible to find a piece for guitar solo. The only work from the XIX century, composed by a guitarist from São Paulo that has been found so far. It is noticeable that the guitar repertoire was in consonance with the general repertoire in vogue in the city: polkas, mazurkas and waltzes, the ballroom dances.
Keywords: music in Sao Paulo; guitar in Sao Paulo city; guitar in the 19th century; brazilian guitar